MORAL SUFFERING IN ASSISTANCE TO CHILDBIRTH: SITUATIONS PRESENT IN THE WORK OF NURSES OF OBSTETRIC CENTERS AND MATERNITIES - Biondi,Heitor Silva (2019)
ABSTRACT Objective: to know the situations found in the work of nurses working in maternity hospitals and obstetric centers that can lead to moral suffering. Method: qualitative, exploratory and descriptive study, developed with 14 nurses working in bstetric centers and maternities of two hospitals in southern Brazil. Data were collected from October 2015 to January 2016, through a semi-structured interview, analyzed based on Content Analysis. Results: there was an occurrence of moral distress related to the activities that supplanted nurses’ execution capacity, leading them to prioritize administrative and managerial activities, for which they are charged by the institutions, failing to participate directly in the care, an aspect enhanced by the quantitative nursing professionals. Asymmetric relations of power and conflicting interactions compose an atmosphere of toleration for the autonomy of the nurses, preventing them from acting in harmony with their knowledge and moral values. The fruitless attempts to change the dehumanizing context through advocacy and the visualization of disrespectful, interventionist and violent behaviors against women, generate moral suffering. Conclusion: the plurality of nurse actions, reduced autonomy, disrespect for their practice and the visualization of dehumanizing behaviors generate moral suffering. It is important to seek alternatives so that nurses may act and advocate in line with their moral knowledge and values, in an autonomous and empowered way, aiming to provide a dignified and safe childbirth assistance, and an environment that respects the woman and her autonomy.